2018
DOI: 10.1002/cyto.a.23574
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Native Unpassaged and Culture‐Expanded Mesenchymal Stromal Cells (MSC)

Abstract: Human culture-expanded mesenchymal stromal cells (MSC) are being considered for multiple therapeutic applications because of their regenerative and anti-inflammatory properties. Although a large number of MSC can be propagated from a small initial sample, several lines of evidence indicate that MSC lose their immunosuppressive and regenerative potency aftaer multiple passages. In this report, we use the FACSCAP Lyoplate proteomic analysis system to detect changes in cell surface protein expression of CD45 /CD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…There is a growing substantial interest in identifying MSC proliferation properties for future application in cell therapy and tissue engineering [25,26]. Herein, the growth kinetics and population doubling-time were influenced by age when younger and older donors were compared, as shown by others [27,28].…”
Section: Discussionmentioning
confidence: 92%
“…There is a growing substantial interest in identifying MSC proliferation properties for future application in cell therapy and tissue engineering [25,26]. Herein, the growth kinetics and population doubling-time were influenced by age when younger and older donors were compared, as shown by others [27,28].…”
Section: Discussionmentioning
confidence: 92%
“…Moravcikova et al have recently used a high-throughput cell surface proteomic approach to analyse the changes in cell surface protein expression of CD45-/CD31-/CD34-/CD73+/CD105+ stromal cells in unpassaged BM MSC and subsequently determine the changes in cell surface markers with accompanying passage [103]. The group presented that the adhesion molecule CD106/VCAM1 is highly expressed in unpassaged MSC but decreases drastically with culture.…”
Section: Cell Surface Proteinsmentioning
confidence: 99%
“…Also for migration of MSCs, a metalloprotease associated with cell motility, CD10/neprilysin, has been shown to be rapidly upregulated in culture but decreased with early senescence [103]. Whereas no consensus yet exists in relation to a specific expression of classical MSC surface molecules on senescent MSCs, recent studies have identified new molecules such as cell surface protein DPP4 and membrane-bound vimentin to identify senescent cells [107,108].…”
Section: Cell Surface Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…We are presently exploring the question of why some populations of MSC are easily dislodged or possibly free floating in the BM, while others remain tightly adhered to the bone/connective tissue matrix and can only be liberated by enzymatic digestion. Determining differences, if they exist, is complicated by the relatively low frequency (<0.01%) of these cells, making them problematic to characterize using common analytical tools, such as flow cytometry, without first expanding in culture, which induces phenotypic and functional alterations [38][39][40][41][42][43][44][45][46]. One previous report found that freshly isolated enzymatic digests of pelvic region trabecular bone contained 15-fold higher CFU-F than aspirated BM [24]; however, we did not find a similar difference between freshly isolated vBA-MSC and BM-MSC.…”
Section: Discussionmentioning
confidence: 99%